Student-Run Clinic Mental Health Services - Morrison, Joseph; Nagayama, Nicole; Tran, Darlene; Lodigiani, Alyse; Sujith, Jeetu; Richards, Kate; Agnoli, Alicia (Journal of Student-Run Clinics, 2025)
Introduction: Student-run clinics (SRCs) are a critical healthcare resource in Sacramento for people experiencing homelessness, people who inject drugs (PWID), and uninsured people. University of California, Davis (UC Davis) School of Medicine-affiliated SRCs are staffed by volunteer students and physicians to serve the Sacramento community at no cost to the patient. Two of these clinics, Willow Clinic and Joan Viteri Memorial Clinic (JVMC), host a free, joint mental health care clinic to support the psychiatric needs of their overlapping patient populations. This descriptive report details the Willow Clinic and JVMC mental health clinic model, reflecting on the three years of operation to provide critical operational insights to other medical schools operating similar clinics in their communities. Methods: At Willow Clinic and JVMC, patients presenting for care at the general medical clinic were offered standardized mental health screening utilizing a Patient Health Questionnaire-9 survey and a Generalized Anxiety Disorder-7 survey. Those who screened positive in either tool were offered to be scheduled for a Mental Health Clinic (MHC) appointment. Patient feedback and MHC attendance trends were utilized to revise the clinic workflow iteratively. Results: In the SRCs, over 90% of patients are screened, but only 8.3% of patients screening positive attend MHC appointments. Though there are strengths in this approach relating to screening, the weaknesses relating to patient retention are iteratively being addressed to improve utilization. Conclusion: People experiencing homelessness, people who use injection drugs, and uninsured patients face a disproportionate burden of barriers to mental health care. The MHC, through two partner SRCs at UC Davis, provides an opportunity to reduce some of these barriers to mental healthcare. This innovative model has promoted health equity in the Sacramento community and is a possible model for other similar SRCs to better serve their communities.